Truncated areas under the curve in the assessment of pioglitazone bioequivalenceData from a single-center, single-dose, randomized, open-label, 2-way cross-over bioequivalence study of two formulations of pioglitazone 45 mg tablets under fasting conditions - Almeida, Susana; Filipe, Augusto; Neves, Rita; Pinho, Catalina; Pedroso, Pedro; Castillo, Araceli; Trabelsi, Fethi (Arzneimittelforschung, 2011)
Pioglitazone (CAS 112529-15-4 for the HCl form) is an oral antidiabetic agent that is a member of the group of drugs known as thiazolidine-diones. It is indicated for the treatment of type 2 diabetes mellitus.The aim of this study was to assess the bioequivalence of a new pioglitazone 45 mg formulation (test formulation) vs. the reference product, as required by European regulatory authorities for the marketing of a generic product. Additionally, the applicability of the truncated area under the plasma concentration curve (AUC) approach to this drug and under these test conditions was determined.This was a single-center, randomized, single-dose, open-label, 2-way crossover study in healthy volunteers under fasting conditions. Plasma samples were collected up to 120 h post-dosing. Pioglitazone and hydroxypioglitazone plasma levels were determined by reverse liquid chromatography and by tandem mass spectrometry detection (LC-MS/MS). Pharmacokinetic parameters were calculated using non-compartmental analysis. Area under the concentration-time curve from time zero to time of last non-zero concentration (AUClast) and maximum observed concentration (Cmax) were the main evaluation criteria, while the area under the concentration-time curve from time zero to infinity (AUCinf) was also analyzed for additional information. For the assessment of the applicability of the truncated AUC approach, AUCs truncated at 24, 48, 72, 96, and 120 h were calculated. All of the abovementioned pharmacokinetic parameters were analyzed using 90% geometric confidence interval of the ratio (T/R) of least-squares means from the ANOVA of the ln-transformed parameter. Tolerability was monitored using physical examination, including vital sign measurements and laboratory analysis. Results: According to the classical approach, the 90% geometric confidence intervals obtained by ANOVA for AUClast, Cmax and AUCint were within the predefined ranges (80–125%) for both ana-lytes. Truncated AUCs were also in all cases within the predefined ranges for acceptance of bioequivalence (e. g. 90% confidence interval).Bioequivalence between test and reference formulations, both in terms of rate and extension of absorption, under fasting conditions was concluded according to European guidelines. Both formulations were well tolerated. The conclusion of bioequivalence was also supported using the truncated AUCs approach.
Keywords: Bioequivalence; CAS 112529-15-4; Pharmacokinetics; Pioglitazone, generic; Truncated AUC